A RETOMADA ANAFÓRICA NOS TEXTOS DE LEITORES PRINCIPIANTES: UMA ANÁLISE DE CASO - STEINKE, MARIA F. L. H.; SANTOS, ROSITA D. S.; STEINKE, MARIA F. L. H.; SANTOS, ROSITA D. S. (Salão do Conhecimento, 2013)
Resumo